2003
DOI: 10.1046/j.1528-1157.2003.63702.x
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Short‐term Prognosis of Status Epilepticus in Adults in Bologna, Italy

Abstract: Summary: Purpose: To determine the incidence and the 30-day case fatality of status epilepticus (SE) in the adult resident population of the city of Bologna, Italy.Methods: Over a 1-year period (March 1, 1999 to February 29, 2000, all patients older than 20 years with SE were included. The case-finding method was based on (a) a prospective surveillance of all public general hospitals in the city by neurologic units, and (b) a review of all discharge codes concerning epilepsy.Results: The crude and standardize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
167
11
5

Year Published

2004
2004
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 228 publications
(200 citation statements)
references
References 14 publications
17
167
11
5
Order By: Relevance
“…Similar high frequency of acute symptomatic aetiology was reported in the hospital-based series in developing countries [8,9,11,13]. Of the acute symptomatic aetiology, cerebrovascular disease is the predominant cause in developed countries [17,18], whereas in developing countries CNS infections accounted for 28-67% of aetiological spectrum [9,12] and this was much more so in the paediatric age group [8,9]. In the studies from developed countries, the reported frequency of CNS infections as the risk factor varied from 4% to 19% [14].…”
Section: Resultssupporting
confidence: 72%
“…Similar high frequency of acute symptomatic aetiology was reported in the hospital-based series in developing countries [8,9,11,13]. Of the acute symptomatic aetiology, cerebrovascular disease is the predominant cause in developed countries [17,18], whereas in developing countries CNS infections accounted for 28-67% of aetiological spectrum [9,12] and this was much more so in the paediatric age group [8,9]. In the studies from developed countries, the reported frequency of CNS infections as the risk factor varied from 4% to 19% [14].…”
Section: Resultssupporting
confidence: 72%
“…(10) This difference in the result is probably due to better health status of children of developed countries and higher rates of infection in developing countries. Of the acute symptomatic etiology, cerebrovascular disease is the predominant cause in developed countries (12,13) whereas in developing countries CNS infections accounted for 28-67% of etiological spectrum (14,15) and this was much more so in the children (14) . In this study 71.5% patients aged less than 2 years were presented status epilepticus with fever.…”
Section: Resultsmentioning
confidence: 99%
“…However, subsequent European studies have shown that CPSE amounts to 16 43% of all SE cases [Vignatelli et al 2003;Knake et al 2001;Coeytaux et al 2000].…”
Section: Cpsementioning
confidence: 99%